A Rare Complication of Silicone Breast Implant Rupture - Sateesh Sakhamuri; Kabeer Ali; Vijay Naraynsingh; Ian Ramnarine; Surujpal Teelucksingh (Annals of Internal Medicine: Clinical Cases)
Rupture of silicone breast implants is common with the time spent in situ but often goes undetected. We encountered a 55-year-old woman who presented with symptoms attributable to hypercalcemia after undergoing the removal of ruptured silicone breast implants. Investigations uncovered multiple enlarged intrathoracic lymph nodes accompanied by extensive granulomatous disease. Although systemic steroids helped to regulate her symptomatic hypercalcemia, it resurfaced on cessation of therapy. This patient's case underscores the necessity of monitoring silicone breast implants and being vigilant for complications that may arise from their rupture.